Late HIV diagnosis and missed opportunities for testing: piloting a standardised, multi-source review process. (March 2020) - Horsley Downie, J; Pegler, M; Widdrington, J; Price, DA; Premchand, N; Chadwick, DR
Late diagnosis of human immunodeficiency virus (HIV) (CD4 < 350) remains common in the UK and missed opportunities (MOs) for testing are often evident. National guidelines recommend HIV clinics conduct look-back reviews in all patients presenting late; however, a standardised methodology is not available and reviews are not routinely performed. This multi-centre audit reviewed all new, late HIV diagnoses across three centres in North East England. A standardised review process (incorporating a shared regional pathology system and summary care records) was used to identify MOs. Of 45 late diagnoses reviewed (median age 45 years, 76% male, median CD4 cell count 134), 28 (62%) had one or more MO, with a median of 18 months from MO to presentation. Sixty-two per cent of MOs occurred in primary care and most (82%) consisted of indicator conditions. At HIV presentation, 27 (60%) suffered moderate harm, 16 (36%) presented with acquired immune deficiency syndrome (AIDS) and 10 (22%) suffered severe harm, including 3 (7%) who died. Despite challenges in eliciting full medical records, the comprehensive review process described, which incorporates two regional electronic records, was more effective than previous methodologies and identified more MOs. Many people present with late HIV infection or AIDS and increased efforts are needed to improve testing.